(untitled) (Bangladesh Journal of Livestock Research, 2020)
A study was conducted to know effects of dietary oils and calcium salts (Ca-salts) of n-6 and n-3 fatty acid (FA) on feed intake, digestibility, enteric methane and blood metabolic profiles in bull. Four rumen cannulated bulls were used in 4x4 Latin Square Designs and supplied with Napier silage and concentrate mixture. Four dietary treatments were sunflower oil (SFO; n-6), linseed oil (LSO;n-3), Ca-salt of SFO (Ca-SFO; n-6) and Ca-salt of LSO (Ca-LSO; n-3). Oils and salts were mixed with concentrate part of the ration at 3% (w/w). Data were analyzed for ANOVA in 2x2 Factorial arrangements. It was found that, intake of DM (p<0.05), OM (P<0.01) and ADF (p<0.05) were reduced by feeding Ca-salts compared to oil sources. On the other hand, intake of CP (p<0.01) and NDF (p<0.05) was reduced by Ca-salts of n-3 FA only, but not of n-6 FA. The EE intake was affected by both FAs and their sources (p<0.01). Digestibility of DM was found higher (p<0.05) in n-3 FA and further Ca-salts reduced (p<0.05) DM digestibility. The CP (p<0.01) and ADF (p<0.01) digestibility was reduced by Ca-salts of either FA, while NDF digestibility was increased (p<0.01) by Ca-salt only in n-3 FA but not in n-6 FA. Concentrations of plasma glucose, urea nitrogen (BUN), cortisol and IgF-1 were affected neither by FA types nor by its sources (p>0.05). Concentrations of total cholesterol, IgG and insulin were decreased (p<0.01) by Ca-salt of FA, while triglyceride was decreased (p<0.05) by n-6 FA. The HDL was found to increase by n-3 FA (p<0.01) as well as Ca-salts (p<0.01) of both FA, but LDL was decreased by n-3 FA (p<0.01) as well as Ca-salts (p<0.01) of both FA. Methane production (% of total gas) were significantly reduced (p<0.01) by n-3 FA at 0 and 4 h after feeding, but not at 2h, while Ca-salts irrespective of FA reduced (p<0.05) methane in all different time periods. Oil sources compared to Ca-salts. In conclusion, Ca-salts of FAs hampered nutrient digestibility but helped to improve lipid profiles in plasma by reducing total cholesterol and LDL, but increasing HDL. Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 34-42